PREPARASI NANOPARTIKEL KURKUMIN MENGGUNAKAN KITOSAN RANTAI SEDANG DAN UJI CELLULAR UPTAKE PADA KULTUR SEL T47D SECARA IN VITRO - , Yos Banne. S.Si., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Curcumin has various of biological activities with broad spectrum, but it has low solubility in water resulting in low systemic bioavailability. This study aims to formulate curcumin nanoparticles with medium-chain chitosan as a carrier which is known to be stable, safe and able to enter the cells. Preparation of curcumin-chitosan nanoparticles prepared by ionic gelation method in an acetate buffer pH 4 and 5. Characterization was due to measure the particle size and zeta potential, morphology of nanoparticle and to determined its entrapment efficiency. The nanoparticle stability is determined by measuring the free curcumin released in artificial intestinal fluid (AIF). The toxicity determined by MTT method with Vero cells as the cell culture model. The cellular uptake on T47D cells was observed using a fluorescent microscope. The nanocurcumin prepared in acetate buffer pH 4 have an average diameter of 563.77 nm with a zeta potential (+) 23 mV, the entrapment efficiency is 70.25 to 90.02% and the stability in the AIF is 83,61 % to 85,36 %. MTT test showed that nanocurcumin is not toxic to the Vero cell with viability > 80 % , and observation by fluorescence microscopy showed that nanocurcumin is able to enter the cell. Based on the results, it is concluded that nanoparticle formulations of curcumin with medium-chain chitosan as a carrier is safe, stable and is able to enter the cell.